2017
DOI: 10.1002/celc.201700672
|View full text |Cite
|
Sign up to set email alerts
|

Specific Ion Effects on the Mediated Oxidation of NADH

Abstract: The electrochemical mediated oxidation of dihydronicotinamide adenine dinucleotide (NADH) by 2,2‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS) was examined in a range of electrolytes. Changes in the Faradaic response were observed that were dependent on the nature of the salt used. In the presence of 200 mM chloride salts, the Faradaic response followed the trend Na+>K+>Li+>Cs+>Gnd+ while in the presence of 200 mM sodium salts, the trend Cl−>Br−>F−>ClO4−>SCN− was observed. The observed trends varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…42 Since the data in Figure 3 indicate that cations only slightly affect the specific activity of ADH, it can be assumed that cofactor-enzyme binding does not play a significant role on the overall rate of reaction. However, recent work has shown that the electrochemical properties of the NAD + /NADH couple are ion specific, 43 therefore the role of the ions with respect to the cofactor cannot be excluded a priori.…”
Section: Resultsmentioning
confidence: 99%
“…42 Since the data in Figure 3 indicate that cations only slightly affect the specific activity of ADH, it can be assumed that cofactor-enzyme binding does not play a significant role on the overall rate of reaction. However, recent work has shown that the electrochemical properties of the NAD + /NADH couple are ion specific, 43 therefore the role of the ions with respect to the cofactor cannot be excluded a priori.…”
Section: Resultsmentioning
confidence: 99%
“…The direct regeneration of nicotinamide coenzymes at unmodified electrode surfaces requires the use of high overpotentials that can result in the formation of dimers of NAD(P) + that are enzymatically inactive. Mediators such as methylene green, methylene blue [39][40][41][42], 2,2-azino-bis-(3-ethyl-benzo-thiazoline-6-sulfonic acid (ABTS) [43], naphthoquinone [44], ferrocenes [45,46], and viologens [47] are widely used to regenerate NAD + , etc. For example; an indirect NAD(P) + regeneration system utilised ABTS to oxidise alcohols with a turnover of 1200 h −1 [48].…”
Section: Mediated Electron Transfermentioning
confidence: 99%
“…Buffers are important in chemistry and biology for their role in pH regulation. However, it is mostly neglected that buffer species can interact specifically at interfaces [1] in the same way that strong electrolytes are known to do [2][3][4][5][6][7][8]. According to the Henderson-Hasselbalch equation [1], the desired pH can be determined solely through the pKa and the concentrations of the weak electrolyte and its conjugated acid/base with the buffer species assumed to have no, or minimal, influence on the system [9,10].…”
Section: Introductionmentioning
confidence: 99%